Enhanced Gas Sensing Performance of Organic Field‐Effect Transistors by Modulating the Dimensions of Triethylsilylethynyl‐Anthradithiophene Microcrystal Arrays. Issue 4 (7th January 2020) - Kwak, Do Hun; Seo, Yena; Anthony, John E.; Kim, Seunghyun; Hur, Jiyeon; Chae, Huijeong; Park, Hui Joon; Kim, Bong‐Gi; Lee, Eunho; Ko, Sunglim; Lee, Wi Hyoung
Abstract: This paper systematically compares the gas sensing properties of organic field‐effect transistors (OFETs) based on patterned 5, 11‐bis(triethylsilylethynyl)anthradithiophene (TES‐ADT) films, by adopting TES‐ADT crystal arrays of various shapes and dimensions. The patterning and crystallization of spin‐cast TES‐ADT layers are achieved by the use of a solvent‐containing engraved polydimethylsiloxane (PDMS) mold. Decreasing width of the TES‐ADT pattern enhances gas sensing performance, as well as field‐effect mobility of OFETs. The decreased grain boundary density at narrower line width contributes to the increase of field‐effect mobility. On the other hand, the increased sensing performance is mainly due to the increased area of crystal edges, which provides a diffusion pathway for gas molecules to arrive at the semiconductor‐dielectric interface. This study provides new perspectives on the diffusion pathway of gas molecules in OFET‐based gas sensor, and will be useful for the design of active channel to boost the gas sensing properties of OFETs. Abstract : Gas sensing properties of the 5, 11‐bis(triethylsilylethynyl)anthradithiophene (TES‐ADT) field‐effect transistor (FET) devices are examined by patterning the TES‐ADT layer in the form of microcrystal arrays. The edge portions of the arrays can provide an accessible pathway for gas molecules to diffuse into the interface between the organic semiconductor and the gate dielectric, thereby increasing both response and recovery rates.